2015
DOI: 10.1002/ange.201500416
|View full text |Cite
|
Sign up to set email alerts
|

Controlling the Origins of Inflammation with a Photoactive Lipopeptide Immunopotentiator

Abstract: Inflammatory immune responses are mediated by signaling molecules that are both produced and recognized across highly heterogeneous cell populations. As such, studying inflammation using traditional immunostimulants is complicated by paracrine and autocrine signaling that obscures the origin of a propagating response. To address this challenge, we developed a small molecule probe that can photosensitize immune cells allowing for light-mediated inflammation. We use this probe to control the origin of inflammati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…As the agonist stays colocalized, we can have the spatial control of agonist presentation and immune cell activation. 16 In initial experiments, we observed that high concentration of the TRIGIR compound, NPPOC-Pam 2 CSK 4 (1, Figure 1a), incubation overnight resulted in higher amount of labeling of the agonist (Figure 1d). However, this also resulted in higher background activation of the cells (Figure 1e).…”
Section: A Cell Labeling With Nppoc-pam 2 Cskmentioning
confidence: 89%
See 1 more Smart Citation
“…As the agonist stays colocalized, we can have the spatial control of agonist presentation and immune cell activation. 16 In initial experiments, we observed that high concentration of the TRIGIR compound, NPPOC-Pam 2 CSK 4 (1, Figure 1a), incubation overnight resulted in higher amount of labeling of the agonist (Figure 1d). However, this also resulted in higher background activation of the cells (Figure 1e).…”
Section: A Cell Labeling With Nppoc-pam 2 Cskmentioning
confidence: 89%
“…[11][12][13][14][15] Recently, we developed a method to tag and remotely induce a guided immune response (TRIGIR) with a photo-caged TLR2/6 agonist. 16 TRIGIR allows for selective labeling of cells, followed by remote light activation. Here we use the TRIGIR method for in vivo light-based activation to control the migration of dendritic cells.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12][13][42][43][44][45][46] Deiters and coworkers previously demonstrated reversible photocaging strategies for enzymes based on nitrobenzyl linkages, 47 while Esser-Kahn and coworkers have demonstrated related approaches to photo-activate smaller lipopeptide Toll-like receptor (TLR) agonists. 48,49 Likewise, Garcia, 50 Hubbell, 51 and Wittrupp 52 have recently developed affinity-targeted cytokine fusions with high cell-or tissue-specific activity. Combining elements of these approaches, here we describe a bioinspired strategy for polymer-induced cytokine latency and photo-induced reactivation.…”
Section: P R E P R I N T C O P Ymentioning
confidence: 99%
“…Preliminary reports have also described how optogenetics may be used to study cancer (5,133), fertilization (42), insulin secretion (9,43,44), endothelial regulation of vasoconstriction (50), and immune function (134), opening the door to a diverse host of targets for manipulation ( Fig. 3).…”
Section: Nonneural Targetsmentioning
confidence: 99%